Carbon Fluxes and Primary Magma CO2 Contents Along the Global Mid‐Ocean Ridge System. (14th March 2019) - Le Voyer, Marion; Hauri, Erik H.; Cottrell, Elizabeth; Kelley, Katherine A.; Salters, Vincent J. M.; Langmuir, Charles H.; Hilton, David R.; Barry, Peter H.; Füri, Evelyn
Abstract: The concentration of carbon in primary mid‐ocean ridge basalts (MORBs), and the associated fluxes of CO2 outgassed at ocean ridges, is examined through new data obtained by secondary ion mass spectrometry (SIMS) on 753 globally distributed MORB glasses. MORB glasses are typically 80–90% degassed of CO2 . We thus use the limited range in CO2 /Ba (81.3 ± 23) and CO2 /Rb (991 ± 129), derived from undegassed MORB and MORB melt inclusions, to estimate primary CO2 concentrations for ridges that have Ba and/or Rb data. When combined with quality‐controlled volatile‐element data from the literature ( n = 2, 446), these data constrain a range of primary CO2 abundances that vary from 104 ppm to 1.90 wt%. Segment‐scale data reveal a range in MORB magma flux varying by a factor of 440 (from 6.8 × 10 5 to 3.0 × 10 8 m 3 /year) and an integrated global MORB magma flux of 16.5 ± 1.6 km 3 /year. When combined with CO2 /Ba and CO2 /Rb‐derived primary magma CO2 abundances, the calculated segment‐scale CO2 fluxes vary by more than 3 orders of magnitude (3.3 × 10 7 to 4.0 × 10 10 mol/year) and sum to an integrated global MORB CO2 flux of 1.32 0.85 + 0.77 × 10 12 mol/year. Variations in ridge CO2 fluxes have a muted effect on global climate; however, because the vast majority of CO2 degassed at ridges is dissolved into seawater and enters the marine bicarbonate cycle. MORB degassing would thus only contribute to long‐term variations in climate via degassing directly into the atmosphere in shallow‐water areas or where the ridge system is exposed above sea level. Plain Language Summary: Estimated CO2 contents of primary mid‐ocean ridge basalts (MORB), calculated on a segment‐by‐segment basis, vary from 104 ppm to 1.9 wt%. CO2 ‐enriched MORB are present in all ocean basins, in particular, in the Atlantic Ocean basin, which is younger and more likely to contain admixed material from recent subduction compared to the much older Pacific Ocean basin. CO2 fluxes at individual ridge segments vary by 3 orders of magnitude due primarily to large variability in primary CO2 content. This study provides the most detailed and accurate estimate to date of the integrated total flux of CO2 from mid‐ocean ridges of 1.32 0.85 + 0.77 × 10 12 mol/year. Key Points: New analyses (753) and compiled data (2, 446) for volatiles CO2, H2 O, F, S, and Cl are reported in a global suite of mid‐ocean ridge basalts Estimated primary MORB CO2 contents vary from 104 ppm to 1.9 wt% and are the result of variations in mantle composition High CO2 fluxes at ridges correlate with high primary CO2 contents and are due to the presence of subduction components in MORB sources